2016
DOI: 10.1371/journal.pone.0157539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-Composting Cattle Manure with Construction and Demolition Waste on the Archaeal, Bacterial, and Fungal Microbiota, and on Antimicrobial Resistance Determinants

Abstract: Agricultural operations generate large quantities of manure which must be eliminated in a manner that is consistent with public health guidelines. Meanwhile, construction and demolition waste makes up about 25% of total solid municipal waste. Co-composting of manure with construction and demolition waste offers a potential means to make manure safe for soil amendment and also divert construction and demolition waste from municipal landfills. Therefore, the archaeal, bacterial, and fungal microbiota of two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 57 publications
(84 reference statements)
4
15
0
1
Order By: Relevance
“…Of the six resistance determinants detected, the proportion of tet (M) and tet (W) was affected by antibiotic treatment in both fecal and NP samples. These two genes were also more relatively abundant in all groups at day 34 compared to day 0. tet (M) and tet (W) are abundant in fecal [56] and manure [57] samples from feedlot cattle and also in the airborne particulate matter of the feedlot environment [58], demonstrating the potential for transmission in feedlots. Both oxytetracycline and tulathromycin increased the proportion of resistance determinants in the NP microbiome, albeit at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six resistance determinants detected, the proportion of tet (M) and tet (W) was affected by antibiotic treatment in both fecal and NP samples. These two genes were also more relatively abundant in all groups at day 34 compared to day 0. tet (M) and tet (W) are abundant in fecal [56] and manure [57] samples from feedlot cattle and also in the airborne particulate matter of the feedlot environment [58], demonstrating the potential for transmission in feedlots. Both oxytetracycline and tulathromycin increased the proportion of resistance determinants in the NP microbiome, albeit at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Euryarchaeota is recognized as the most abundant archaeal phylum in ruminants (Kumar et al, 2015 ; Danielsson et al, 2017 ; Zhou et al, 2017 ). Methanobrevibacter is reported to be the most abundant archaeal genus in the rumen as well as in most samples from dairy feces (Kumar et al, 2015 ; Holman et al, 2016 ). However, our study found that both Methanobrevibacter and Methanocorpusculum were predominant in the feces of Holstein dairy heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal waste-streams contain antibiotic resistant bacteria (ARBs), ARGs, antibiotics, metals, and other potential agents that could exert selection pressure for AMR. Depending on how the waste is treated and handled, resistance levels can increase or decrease (Marti et al, 2013;Larson, 2015;Bengtsson-Palme et al, 2016;Bondarczuk et al, 2016;Holman et al, 2016;Qian et al, 2016). Ideally, sanitation technologies can be adapted to serve their intended purpose of minimizing human exposure to fecal pathogens, while also reducing the potential spread of ARGs to human pathogens or to the reservoir of resistance in the natural human, aquatic, and soil microbiomes.…”
Section: Transmission Of Argsmentioning
confidence: 99%